Hubungan Sikap Ibu dengan Pelaksanaan Metode Kangguru (Kangaroo Mother Care) pada Bayi Berat Badan Lahir Rendah di RS Siti Khodijah Sepanjang: The Relationship of Mother's Attitude with the Implementation of the Kangaroo Mother Care Method in Low Birth Weight Babies at Siti Khodijah Hospital Throughout - Kusumawardani, Paramitha Amelia; Cholifah, Cholifah (Jurnal Kebidanan Midwiferia, 2018)
Problems that often occur are setting the temperature that is still low and has a weak immune system and the process of forming the immune system that is not perfect so that the range of infection. Not all babies with a birth weight of less than 2,500 grams get health services using advanced technology because of financial constraints in care, geographical factors or areas of residence, transportation, and communication such as the use of incubators. The kangaroo treatment method is a method of contacting skin from skin (skin to skin) which is done directly by placing the baby on the mother's chest. The method of research carried out analytic research with a population of all mothers who have given birth either by normal or SC deliveries whose babies experience low body weight below less than 2500 grams (LBW) in SitiKhodijahSepanjang Hospital, which is the subject of research. Most of the mothers who had LBW babies had a positive attitude that was equal to 10 (66.7%) and most of the mothers carried out the kangaroo method correctly by 9 mothers (60%). This is also evidenced by the results of the Chi-Square test P = 0.005 <α = 0.05 so that H0 is rejected which means there is a relationship between the attitude of the mother and the implementation of the kangaroo method in low birth weight babies so that the community and health workers are expected to implement the kangaroo method infants low birth weight both health care and at home.